Focal treatment of spasticity using botulinum toxin A in cerebral palsy cases of GMFCS level V: evaluation of adverse effects - Ana Paula Tedesco; Juliana Saccol Martins; Renata D'Agostini Nicolini-Panisson (Revista Brasileira de Ortopedia, 2014)
Objective:To report on the experience of injections of botulinum toxin A (BTA) in a series of patients with cerebral palsy of Gross Motor Function Classification System (GMFCS) level V.Methods:This was a retrospective case series study on 33 patients with cerebral palsy of GMFCS level V who received 89 sessions of BTA application (of which 84 were Botox® and five were other presentations), in which the basic aim was to look for adverse effects.Results:The mean number of application sessions per patient was three, and the mean age at the time of each injection was 4 + 6 years (range: 1.6–13 years). The muscles that most frequently received injections were the gastrocnemius, hamstrings, hip adductors, biceps brachii and finger flexors. The mean total dose was 193 U and the mean dose per weight was 12.5 U/kg. Only one patient received anesthesia for the injections and no sedation was used in any case. No local or systemic adverse effects were observed within the minimum follow-up of one month.Conclusion:The absence of adverse effects in our series was probably related to the use of low doses and absence of sedation or anesthesia. According to our data, BTA can be safely used for patients with cerebral palsy of GMFCS level V, using low doses and preferably without sedation or anesthesia.